Ways and Problems of Financing Public Education Institutions - Farhod Karimov (International Journal on Orange Technologies, 2021)
One of the main socio-economic issues of the states is the problem of financing education. In almost all countries, education is considered a state-funded service. However, many developing countries face a number of challenges in funding education. These problems are, firstly, the lack of sufficient financial resources for education, and secondly, the lack of competencies to effectively use available resources.